2001
DOI: 10.1034/j.1600-0447.2001.00258.x
|View full text |Cite
|
Sign up to set email alerts
|

Birth order and risk for schizophrenia: a 31‐year follow‐up of the Northern Finland 1966 Birth Cohort

Abstract: Objective: The Northern Finland 1966 Birth Cohort was studied in order to investigate the association between birth order and schizophrenia. Method: Four categories of birth order status (®rst-born, last-born, only child and other status) were formed and linked to data on psychiatric morbidity. Effects were adjusted for wantedness of pregnancy, perinatal complications, maternal age at delivery, family type and number of siblings. Results: The risk for schizophrenia was elevated among male ®rst-borns (ratio 1.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 21 publications
4
18
1
Order By: Relevance
“…On the other hand, a very large scale Danish cohort study involving 2669 cases showed no effect for birth order [12]. A significantly higher risk for first-born males was reported from a Finnish cohort study with 100 cases [13], and in accordance with this, a recent study from Pakistan with 453 cases reported highly significant excess of firstborns among patients with schizophrenia [14]. …”
Section: Introductionmentioning
confidence: 73%
“…On the other hand, a very large scale Danish cohort study involving 2669 cases showed no effect for birth order [12]. A significantly higher risk for first-born males was reported from a Finnish cohort study with 100 cases [13], and in accordance with this, a recent study from Pakistan with 453 cases reported highly significant excess of firstborns among patients with schizophrenia [14]. …”
Section: Introductionmentioning
confidence: 73%
“…Additionally, examining potential correlates that were not included here, including parental disorder, education, or marital status may provide valuable information into the nature of the associations that we have found. Examination of birth order, 53 interval, 54 or difference in parental ages 55 may also be informative to elucidate mechanisms underlying the parental age effect. Finally, assessment of genetic markers that may underlie the parental age phenomena, specifically de novo mutations, may be a beneficial line of inquiry.…”
Section: Discussionmentioning
confidence: 99%
“…However, many complex disorders have been associated with birth order [1][2][3][4][5][6][7][8][9]70], which argues in favor of a true biological factor. There is no clear evidence of any genetic factor being directly modified by later birth order.…”
Section: Discussionmentioning
confidence: 99%